Regulation of the Bone Vascular Network is Sexually Dimorphic. (9th October 2019) - Goring, Alice; Sharma, Aikta; Javaheri, Behzad; Smith, Rosanna CG; Kanczler, Janos M; Boyde, Alan; Hesse, Eric; Mahajan, Sumeet; Olsen, Bjorn R; Pitsillides, Andrew A; Schneider, Philipp; Oreffo, Richard OC; et al.
ABSTRACT: Osteoblast (OB) lineage cells are an important source of vascular endothelial growth factor (VEGF), which is critical for bone growth and repair. During bone development, pubertal differences in males and females exist, but little is known about whether VEGF signaling contributes to skeletal sexual dimorphism. We have found that in mice, conditional disruption of VEGF in osteocalcin‐expressing cells (OcnVEGFKO) exerts a divergent influence on morphological, cellular, and whole bone properties between sexes. Furthermore, we describe an underlying sexual divergence in VEGF signaling in OB cultures in vitro independent of circulating sex hormones. High‐resolution synchrotron computed tomography and backscattered scanning electron microscopy revealed, in males, extensive unmineralized osteoid encasing enlarged blood vessel canals and osteocyte lacunae in cortical bone after VEGF deletion, which contributed to increased porosity. VEGF was deleted in male and female long bone–derived OBs (OBVEGKO) in vitro and Raman spectroscopic analyses of mineral and matrix repertoires highlighted differences between male and female OBVEGFKO cells, with increased immature phosphate species prevalent in male OBVEGFKO cultures versus wild type (WT). Further sexual dimorphism was observed in bone marrow endothelial cell gene expression in vitro after VEGF deletion and in sclerostin protein expression, which was increased in male OcnVEGFKO bones versus WT. The impact of altered OB matrix composition after VEGF deletion on whole bone geometry was assessed between sexes, although significant differences between OcnVEGFKO and WT were identified only in females. Our results suggest that bone‐derived VEGF regulates matrix mineralization and vascularization distinctly in males and females, which results in divergent physical bone traits.